Design of electrical transmission lines structures and foundations - Kalaga, Sriram; Yenumula, Prasad (CRC Press/Taylor & Francis, 2017)
The book is aimed at students, practicing engineers, researchers and academics. It will contain beneficial information to those involved in the design and maintenance of transmission line structures and foundations.